CORTICO‐LIMBIC RESPONSES TO MASKED AFFECTIVE FACES ACROSS PTSD, PANIC DISORDER, AND SPECIFIC PHOBIA. Issue 2 (16th July 2013) - Killgore, William D. S.; Britton, Jennifer C.; Schwab, Zachary J.; Price, Lauren M.; Weiner, Melissa R.; Gold, Andrea L.; Rosso, Isabelle M.; Simon, Naomi M.; Pollack, Mark H.; Rauch, Scott L.
<x xml:space="preserve">Abstract</x> Background Exaggerated amygdala and reduced ventromedial prefrontal cortex (vmPFC) responsiveness during emotional processing have been reported in studies examining individual anxiety disorders. Studies are needed, however, which directly compare activation of amygdalo‐cortical circuitry across multiple anxiety disorders within the same study. Here we compared cortico‐limbic neurocircuitry across three different anxiety disorders using a well‐validated emotional probe task. Methods Sixty‐five adult volunteers, including 22 healthy controls (HC) and participants meeting DSM‐IV criteria for either posttraumatic stress disorder (14 PTSD), panic disorder (14 PD), or specific animal phobia (15 SP), underwent functional magnetic resonance imaging (fMRI) at 3 T while passively viewing backward‐masked images of faces expressing fear, happy, and neutral emotions. Results A group comprising all three anxiety disorders showed greater activation within the left amygdala and reduced activation within the vmPFC compared to the HC group during the masked fear versus neutral condition. Pairwise group comparisons showed that amygdala activation only reached significance for the PTSD versus HCs, whereas decreased vmPFC was only evident for SP and PD groups versus the HC group. Furthermore, activation did not differ among the anxiety groups when contrasted directly with one another. A similar pattern was observed for masked happy versus neutral faces. Conclusions Exclusive of specific diagnostic category, anxiety disorders were generally associated with increased activation of the amygdala and reduced activation within vmPFC. Categorical distinctions were generally weak or not observed and suggest that functional differences may reflect the magnitude of responses within a common neurocircuitry across disorders rather than activation of distinct systems.